MANAGEMENT OF NEW STUDENT ADMISSIONS IN IMPROVING THE QUALITY OF GRADUATES AT SMP ISLAM AL-ULUM TERPADU MEDAN - Hasrian Rudi Setiawan; Abd. Mukti; Syaukani Syaukani (Proceeding International Seminar of Islamic Studies, 2021)
This study aims to determine the management of new student admissions in improving the quality of graduates at SMP Islam Al-Ulum Terpadu Medan. This research uses qualitative research methods with a phenomenological approach. The data collection techniques used were: observation, interviews, and documentation study. Data analysis was carried out by using the following techniques: selection, data presentation, and conclusion drawing. The results of this study indicate that: Planning to improve the quality of graduates at SMP Islam Al-Ulum Terpadu Medan, is carried out by determining the target achievement of student activities to be carried out, determining how to achieve them and identifying the possibilities that will occur in carrying out student activities (student).Keywords: Managemen, New Student Admissions, Quality Of Graduates